To sing with one’s own voice (and to be heard) : Bridges among moral perfectionism and epistemic justice - Gamero, Isabel (Analysis. Journal of Philosophical Research, 2019)
In this paper, I compare Stanley Cavell’s understanding about the scepticism and the drama of the unknown woman with José Medina’s diagnose on epistemic injustice, in order to understand, firstly, how are conducted the processes of silencing and lack of acknowledgement, which harm underrepresented people and collectives. Secondly, I contrast the solutions that Cavell and Medina pose to these problems, with an especial interest in the link they establish among epistemic, ethic and politic elements, and in their regard of arts and emotions, as factors that overflow the Modern and Cartesian understanding of philosophy and play a fundamental role in the overcoming of the aforementioned difficulties. Some artistic examples will be also brought up to illustrate Medina and Cavell’s explanations.